The seasonal assessment of heavy metals pollution in the waters of the Mediterranean and Atlantic seas of Morocco - Karim, S.; Aouniti, A.; Belbachir, C. (European Scientific Journal, ESJ, 2025)
Heavy metal pollution is a topical problem that concerns all communities anxious to maintain their water assets to a certain degree of quality. Heavy metals are not metabolized, they can be transferred into the food chain and accumulate in living matter. Metals, which are normal constituents of the environment, are all toxic above a certain threshold. In order to evaluate the health risk for humans and preserve the environment, we studied the level of metallic pollution (Cd, Pb, Zn, Fe, Cu, Cr and Ni) in water samples from both Moroccan coasts; the Mediterranean Sea (Nador coast), and the Atlantic coast (Casablanca coastline), this samples for the autumn and spring seasons between 2023 and 2024. The results obtained show that the concentrations of the metallic elements studied exceed the standard set by the WHO for certain elements.